2006
DOI: 10.1162/jocn.2006.18.9.1586
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Evidence for Distinct Cognitive and Affective Components of Self

Abstract: Abstract& This study examines whether the cognitive and affective components of self-reflection can be dissociated using functional magnetic resonance imaging. Using a simple paradigm in which subjects judged the personal relevance of personality characteristics that were either favorable (e.g

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

69
398
6
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 463 publications
(478 citation statements)
references
References 25 publications
(37 reference statements)
69
398
6
5
Order By: Relevance
“…The cognitive component of the task (that is 'like me/not like me') engaged the MPFC irrespective of the valence of the trait word, whereas the affective component of the task (that is 'favourable/unfavourable') was resolved in ventral anterior cingulate cortex. 10 Taken together, 7,8,10 the above findings implicate medial frontal, cingulate, parietal cortex and precuneus in tasks that require self-referential processing of personality-trait words.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…The cognitive component of the task (that is 'like me/not like me') engaged the MPFC irrespective of the valence of the trait word, whereas the affective component of the task (that is 'favourable/unfavourable') was resolved in ventral anterior cingulate cortex. 10 Taken together, 7,8,10 the above findings implicate medial frontal, cingulate, parietal cortex and precuneus in tasks that require self-referential processing of personality-trait words.…”
Section: Introductionmentioning
confidence: 91%
“…Recent functional magnetic resonance imaging (fMRI) [7][8][9][10] and Positron Emission Tomography (PET) 11 studies have identified medial prefrontal (MPFC), parietal and occipital cortex as part of an extended network of brain regions involved in the categorization and recognition of positive and negative personality-trait words processed in a selfreferential manner. For example, increased blood oxygenation level-dependent (BOLD) activity in parietal and occipital regions has been hypothesized to reflect enhanced attentional processes to biologically significant or personally relevant events.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mechanisms in the brain that might mediate the influence of our affiliation to a group on our responses to the behavior of another person, have not previously been explored. Notably, the effects are in a similar region to those identified in studies examining self‐related processing, including self‐reflection and studies showing effects of similarity on neural responses when people made judgments about other people (Ames, Jenkins, Banaji, & Mitchell, 2008; Cikara et al., 2014; Jenkins & Mitchell, 2011; Kelley et al., 2002; Mitchell, Macrae, & Banaji, 2006; Moran, Macrae, Heatherton, Wyland, & Kelley, 2006) and also depend on the degree to which individuals shift their behaviors to conform with others (Apps & Ramnani, 2017). This raises the possibility that activity in response to others in this region may become more similar to self when interacting with ingroup members, and that this mergence is greater when an individual is highly fused to the group.…”
Section: Discussionmentioning
confidence: 99%